2021
DOI: 10.1007/s11060-021-03896-3
|View full text |Cite
|
Sign up to set email alerts
|

ERK inhibition in glioblastoma is associated with autophagy activation and tumorigenesis suppression

Abstract: Purpose Autophagy-dependent tumorigenic growth is one of the most commonly reported molecular mechanisms in glioblastoma (GBM) progression. However, the mechanistic correlation between autophagy and GBM is still largely unexplored, especially the roles of autophagy-related genes involved in GBM oncogenesis. In this study, we aimed to explore the genetic alterations that interact with both autophagic activity and GBM tumorigenesis, and to investigate the molecular mechanisms of autophagy involved in GBM cell de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…The levels of intracellular ROS (Figure a,b) and tumor suppressor p53 were significantly elevated, while loss of MMP (Figure c,d) and decreased the expression of B-cell lymphoma 2 (Bcl-2) (Figure a,b), further verified that 4 and 10 significantly induced intrinsic (loss of ΔΨm) apoptotic signaling. In addition, it has been proved that the interplay between the ERK pathway and autophagy can regulate tumor progression . Once the cancer cells are exposed to the autophagic stimuli, the ERK signaling shall be downregulated by the upstream pathways, causing mTOR complex decomposition and beclin-1 and ULK1 upregulation, followed by autophagy initiation .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The levels of intracellular ROS (Figure a,b) and tumor suppressor p53 were significantly elevated, while loss of MMP (Figure c,d) and decreased the expression of B-cell lymphoma 2 (Bcl-2) (Figure a,b), further verified that 4 and 10 significantly induced intrinsic (loss of ΔΨm) apoptotic signaling. In addition, it has been proved that the interplay between the ERK pathway and autophagy can regulate tumor progression . Once the cancer cells are exposed to the autophagic stimuli, the ERK signaling shall be downregulated by the upstream pathways, causing mTOR complex decomposition and beclin-1 and ULK1 upregulation, followed by autophagy initiation .…”
Section: Resultsmentioning
confidence: 99%
“…18 Once the cancer cells are exposed to the autophagic stimuli, the ERK signaling shall be downregulated by the upstream pathways, causing mTOR complex decomposition and beclin-1 and ULK1 upregulation, followed by autophagy initiation. 18 When the ERK signaling pathway is over-suppressed, autophagy might be hyperactivated, which is cytodestructive and catastrophic for cell survival. In the present study, the EVO−Pt(IV) compounds were found to increase autophagy by increasing the expression of ULK1, beclin-1, and LC3-II and suppressing p62 expression, suggesting the cytodestructive role of autophagy induction upon the suppression of ERK signaling produced by 4 and 10.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Phosphorylation of STAT3 at Tyr705 is critical for its homodimerization, nuclear localization, and transactivation, which can promote tumor cell proliferation via enhancing cell cycle-related protein expression [ 21 , 22 ]. While phosphorylation of STAT3 at Ser727 is mediated by extracellular regulated protein kinases (ERK), inhibition of ERK effectively triggers autophagic cell death via an mTOR-dependent pathway in GBM cells [ 23 , 24 ]. Therefore, phosphorylation of the Ser727 and Tyr705 residues is critical for STAT3 in promoting tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%